Soluble Receptor Isoform of IFN-Beta (sIFNAR2) in Multiple Sclerosis Patients and Their Association With the Clinical Response to IFN-Beta Treatment - Aliaga-Gaspar, Pablo; Hurtado-Guerrero, Isaac; Ciano-Petersen, Nicolas Lundahl; Urbaneja, Patricia; Brichette-Mieg, Isabel; Reyes, Virginia; Rodriguez-Bada, Jose Luis; Alvarez-Lafuente, Roberto; Arroyo, Rafael; Quintana, Ester; Ramió-Torrentà, Lluis; Alonso, Ana; et al. (Frontiers in Immunology, 2021)
Purpose Interferon beta receptor 2 subunit (IFNAR2) can be produced as a transmembrane protein, but also as a soluble form (sIFNAR2) generated by alternative splicing or proteolytic cleavage, which has both agonist and antagonist activities for IFN-β. However, its role regarding the clinical response to IFN-β for relapsing-remitting multiple sclerosis (RRMS) is unknown. We aim to evaluate the in vitro short-term effects and after 6 and 12 months of IFN-β therapy on sIFNAR2 production and their association with the clinical response in MS patients. Methods Ninety-four RRMS patients were included and evaluated at baseline, 6 and 12 months from treatment onset. A subset of 41 patients were classified as responders and non-responders to IFN-β therapy. sIFNAR2 serum levels were measured by ELISA. mRNA expression for IFNAR1, IFNAR2 splice variants, MxA and proteases were assessed by RT-PCR. The short-term effect was evaluated in PBMC from RRMS patients after IFN-β stimulation in vitro. Results Protein and mRNA levels of sIFNAR2 increased after IFN-β treatment. According to the clinical response, only non-responders increased sIFNAR2 significantly at both protein and mRNA levels. sIFNAR2 gene expression correlated with the transmembrane isoform expression and was 2.3-fold higher. While MxA gene expression increased significantly after treatment, IFNAR1 and IFNAR2 only slightly increased. After short-term IFN-β in vitro induction of PBMC, 6/7 patients increased the sIFNAR2 expression. Conclusions IFN-β administration induces the production of sIFNAR2 in RRMS and higher levels might be associated to the reduction of therapeutic response. Thus, levels of sIFNAR2 could be monitored to optimize an effective response to IFN-β therapy.